Measuring Bankruptcy Risk in Indonesian Contemporary Industries: Implementing Altman's Z-Score Framework - Pramono, Wisnu Bayuaji; Nugroho, Anggoro Budi (Journal of Business and Management, 2013)
Financial analysis is used to give a broader picture and an understanding of a company business activity and operations. Financial analysis will help investors, creditors and shareholder answers the impending question about the company, Does the company liquidity situation is good? Can the company meet its obligations? Does the company rely too much on the debt? Can the company maximize the profits from its assets? In addition, financial analysis can reduce our reliance on hunches, intuition and guesses and reduces our uncertainty and unwanted when making decisions. Therefore to by using the analytical tools and technique of the financial analysis, one can reduce risk and project the future performance of the company within a given industry. The Altman Z-score model is mathematical for the creditworthiness of the company; the Z-score is a result of scientific investigation into the prediction of a possibility of bankruptcy of a company. This study will aim to find the equation model and the Z-score for each company in Indonesian contemporary using the multiple regressions analysis. The companies used in this research are from each sector in Indonesia Stock Exchange, furthermore the companies are the ones that are included in the LQ-45 from the period February until July 2013. The research will use the Altmanâ€™s framework and use multiple linear regressions to generate model that is compatible for each company. The study results shows that from nine companies that are tested for the Z-score, six of the companies is safe from bankruptcy, but action should be taken to avoid the risk of bankruptcy. The companies are Astra International with Z-score of 2.19, Aneka Tambang with Z-score of 1.89, Sentul City with 2.41, Indofood Sukses Makmur with Z-score of 2.18, Mitra Adiperkasa with 2.33 and Semen Gresik with 1.88. (Z-score 1.81 to 2.99). The other three companies, BW Plantation with Z-score 0.84, Jasa Marga with 0.96 and Bank Danamon with 0.61 is in the distress zones, which means the company can be categorized as highly likely to be bankrupt.Â Keywords: Altman Z-score, bankruptcy, financial analysis, financial ratios.------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.